Association between presence of latrine and unclean child face on the prevalence of active trachoma among children aged 1 to 9 years in low-income setting: A systematic review and meta-analysis - Leykun Berhanu; Chala Daba; Belay Desye; Abebe Kassa Geto; Gete Berihun (PLoS ONE, 2025)
Background Trachoma is the leading infectious cause of blindness worldwide, primarily affecting populations in low-income countries with poor sanitation and hygiene conditions. The World Health Organization has set a goal to eliminate trachoma as a public health problem. However, progress towards this goal has been uneven across different regions. This systematic review and meta-analysis aimed to synthesize the available evidence on the association between the presence of latrine facilities and unclean child faces with the prevalence of active trachoma among children aged 1 to 9 years in low-income country settings. The findings from this study can help guide the design of more targeted interventions to reduce the burden of trachoma in vulnerable populations. Materials and methods A total of 2695 articles were searched from PubMed, Hinari, African Online Journals, Google, Google Scholar, Science Direct, and Semantic Scholar and exported to STATA version 17 for analysis. The levels of heterogeneity among studies were assessed using I2 and p-values. The findings of the meta-analysis were presented using a table, graph, and forest plot with a 95% confidence interval. A P-value of less than 0.05 was considered statistically significant. Result Among 2695 articles searched, 16 of them were selected for meta-analysis. The pooled prevalence of active trachoma was 21.10 (95% CI; 14.18, 28.02). The finding indicated high heterogeneity among the included studies (I2 =99.3%, p<0.0001). There was a statistically significant association between the presence of a latrine (POR=0.10, 95% CI: 0.00, 0.19) and unclean child face (POR=1.30, 95% CI: 1.08, 1.53) and the pooled prevalence of active trachoma among children aged 1 to 9 years in low-income countries. Conclusion The present study revealed that the pooled prevalence of active trachoma was high as compared to the WHO trachoma eradication goal. The presence of latrine facility and unclean child face were significantly associated with the prevalence of active trachoma among children aged 1 to 9 years in low-income countries. Hence it is recommended to improve access to latrines, promote child facial hygiene, and intensify overall trachoma control in low-income countries.